Sustainable Tourism Development in the Content of Curricula in Georgia and Other Foreign Countries (Comparative Study and Analysis) - Koblianidze, Tamar; Sachaleli, Nino (European Scientific Journal, ESJ, 2023)
In recent years, sustainable development has become an important part of educational systems, from schools to universities, making it a societal priority. In 2019, UNESCO adopted the ESD for 2030 framework with the overall objective of building "a more just and sustainable world through the achievement of the 17 Sustainable Development Goals." The Education for Sustainable Development for 2030 framework identifies five priority action areas: policy, education and training settings, educators, youth, and communities. Sustainable tourism development has been a commonly used term for many years and is, therefore, an important concept for consideration within tourism degree courses/programs. Based on qualitative research and a case study method, the article discusses several undergraduate and graduate programs in the context of teaching sustainable tourism, comparing them with the experience of the Georgian Technical University. It is now in its fourth year of implementing an innovative and challenging undergraduate educational program, "Mountain Sustainable Tourism and Hospitality Management." In conclusion, it can be said that sustainable tourism programs are becoming more and more in demand, but the Georgian Technical University program, on an international scale, has no analog and is unique. At the same time, the results indicate that in many cases, sustainability pedagogy/teaching methods and approaches such as systems and holistic thinking are not yet widely used and are still being developed.